The Impact of Multidimensional Innovation on Brand Evangelism: Empirical Evidence from Starbucks - Fajriana Khayatul Zikra; Arry Widodo; Anita Silvianita; Nurafni Rubiyanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Using data from Telkom University Bandung students, this study seeks to determine the relationship between menu innovation, packaging innovation, experience innovation, and consumer engagement and brand evangelism. Utilizing Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) method, the research model is constructed. The findings of the study indicate that brand evangelism can be impacted by consumer engagement, which is reciprocally influenced by multidimensional innovation. The relationship between brand evangelism, menu innovation, packaging innovation, and experience innovation is mediated by customer engagement. This study possesses numerous ramifications for organizations seeking to cultivate brand evangelism. Organizations must persist in their efforts to innovate menus, merchandising, and deliver enhanced consumer experiences